Plasmodium falciparum drug resistance phenotype as assessed by patient antimalarial drug levels and its association with pfmdr1 polymorphisms. - Malmberg, M; Ferreira, P; Tarning, J; Ursing, J; Ngasala, B; Björkman, A; Mårtensson, A; Gil, J (2013)
BACKGROUND: Multidrug-resistant Plasmodium falciparum is a major threat to global malaria control. Parasites develop resistance by gradually acquiring genetic polymorphisms that decrease drug susceptibility. The aim of this study was to investigate the extent to which parasites with different genetic characteristics are able to withstand individual drug blood concentrations. METHODS: We analyzed 2 clinical trials that assessed the efficacy and effectiveness of artemether-lumefantrine. As a proof of concept, we used measured day 7 lumefantrine concentrations to estimate the concentrations at which reinfections multiplied. P. falciparum multidrug resistance gene 1 (pfmdr1) genotypes of these parasites were then correlated to drug susceptibility. RESULTS: Reinfecting parasites with the pfmdr1 N86/184F/D1246 haplotype were able to withstand lumefantrine blood concentrations 15-fold higher than those with the 86Y/Y184/1246Y haplotype. CONCLUSIONS: By estimating drug concentrations, we were able to quantify the contribution of pfmdr1 single-nucleotide polymorphisms to reduced lumefantrine susceptibility. The method can be applied to all long-half-life antimalarial drugs, enables early detection of P. falciparum with reduced drug susceptibility in vivo, and represents a novel way for unveiling molecular markers of antimalarial drug resistance.